Evaluasi penyimpanan barang non medik di sub bagian rumah tangga RSJ Grhasia DIY - Ramjan Yunus; Rochana Ruliyandari (Universitas Ahmad Dahlan, 2020)
The hospital is a health service institution that functions to provide and organize health efforts that are healing and patient recovery. The performance of the goods storage system depends on internal characteristics including, storage capacity, ease of access to the storage location, level of information technology. While external characteristics such as the type of goods, the number of goods, the amount of inventory, and the type of goods flow in and out. The purpose of this study was to evaluate the storage of non-medical goods in the sub-section of the RSJ Grhasia DIY household. The evaluations used are Contex, Input, Process and Product (CIPP) developed by Stufflabeam. This study used a qualitative descriptive method with a Phenomonology design. The technique of taking interview informants is using purposive sampling method with three informants and observing the storage of goods in the warehouse section of the RSJ Grhasia DIY household. Evaluation of the storage of goods in the warehouse of the household section of RSJ Grhasia DIY has not run optimally due to the storage of goods that has not been orderly and neat. Contex's goods storage policy is good as a reference in working. SOP inputs for storing goods are good, human resources are sufficient, funds are good, facilities and infrastructure are not optimal due to the narrow building area. The process of receiving goods has not been optimal due to delays in the delivery of goods and goods that arrive not in accordance with the quantity and specifications. Storage and arrangement of goods is not optimal, due to inadequate warehouse area. Care and care of the goods has been running optimally in accordance with the purpose of storing the goods to be safe and maintained its quality. item inventory taking is going well because the stock card with stock taking is in compliance. Based on the results of the evaluation in the process is not running optimally.